Tampa Skala for Kinesiofobi: Test-retest studie af den danske version på kroniske smertepatienter - Det Digitale Projektbibliotek, Aalborg Universitet - Eiger, Bettina; Sirek, Zerrin Saadet; Errebo, Mette (Aarhus Universitet, 2019)
Introduction: Kinesiophobia is a known predictor for the degree of disability in chronic pain patients. The Tampa Scale of Kinesiophobia(TSK) has been extensively researched and translated into 14 languages. It has been found to be a valid and reliable tool in identifying kinesiofobic beliefs in patients. It has recently been translated into Danish, but to these authors knowledge, not yet tested for reliability. Although it has been implemented into research and in the clinic, there is no consensus on which cut-off score implies a clinically relevant degree of kinesiophobia. We have followed recommendations from COSMIN in planning and reporting this reliability study. Aim and study design: We used a test-retest study design to establish the test-retest reliability of the TSK (Danish version) in a group of chronic pain patients referred to a regional pain center. The patients were stable between tests and received no interventions. Both tests were filled out via e-mail link. The test-retest reliability was calculated using ICC2,1. We investigated measurement error in terms of SEM and SDC and explored existing cut-off scores for TSK-17 and TSK-13. Results: Of 108 eligible patients, 77 were included in the analysis. The mean interval between tests was 8,4 days. We found ICC2,1-values of 0,863 (CI95% 0,790 – 0,911), 0,882 (0,819 – 0,924) and 0,873 (0,807 – 0,918) for TSK-17, TSK-13 and TSK-11. We found SEM-values of 3,08, 2,42 and 2,10 and SDC95%-values of 8,53 (TSK-17), 6,71 (TSK-13) and 5,82 (TSK-11). With the cut-off scores of 40 on the TSK-17 and 31 on the TSK-13, both derived from the median of the population, the scale was found to be stable and reliable, with kappa values of 0,607 (p<0,001) and 0,688 (p<0,001). Conclusion: This study showed that the Danish versions of TSK-17, TSK-13 and TSK-11 have good to excellent test-retest reliability, with small SEM-values and SDC of 8,53, 6,71 and 5,82. With a cut-off derived from the median in TSK-17 and TSK-13, the scale was found stable and there was a tendency towards the patients in TSKhigh feeling more limited due to pain and being less active, lending evidence to the clinical relevance of these cut-off’s. Further research is warranted to confirm these results.